Ciudadela Parque Tenerife, Neiva (Huila) - Gómez Puccini, Juan Pablo (Universidad Antonio Nariño, 2021)
The urban renovation plans consist of the identification of components in a place which are not used or are in a state of deterioration, these plans seek to transform and improve the quality of the places for the inhabitants of the affected area. Over the years, different parts of the world have had to undergo positive and negative changes, which require adaptation and evolution in order to evolve and transform in order to encourage good urban, arc development. hitectural, social and sustainable The purpose of this degree project is to propose a solution for one of the urban voids that the city of Neiva has, such as a large part of the artillery battalion # 9 Tenerife, which is located in the southeast of the city , which seeks to formulate joint solution strategies and use of these spaces to give an adequate use for the opita community.